The interaction between Alternative Healthy Eating Index and MC4R rs17782313 gene variants on central and general obesity indices in women: A cross‐sectional study. Issue 4 (16th June 2022) - Zarei, Mahtab; Shiraseb, Farideh; Mirzababaei, Atieh; Mirzaei, Khadijeh
Abstract: Background: Previous studies have shown that the C allele of melanocortin 4 receptor (MC4R) rs17782313 and the Alternative Healthy Eating Index (AHEI) are separately associated with obesity. However, the present study aimed to investigate the interaction between MC4R rs17782313 variants and the AHEI and their association with central and general obesity indices, which has not been assessed previously. Methods: In total, 291 women with body mass index (BMI) ≥ 25 kg m –2 and aged 18–48 years enrolled in this cross‐sectional study. All participants were assessed for body composition, anthropometric measures, dietary intake, and blood parameters. After obtaining data of dietary intake from the 147‐item food frequency questionnaire, the AHEI was calculated. MC4R rs17782313 single‐nucleotide polymorphisms were assessed using the polymerase chain reaction‐restriction length polymorphism method. Results: After adjustment for age, energy intake, physical activity, marital status, and economic status, the interaction between MC4R rs17782313 and the AHEI was associated with hip circumference [β = −0.41, 95% confidence interval (CI) = −0.77 to −0.05, p  = 0.02], BMI (β = −0.15, 95% CI = −0.29 to −0.02, p  = 0.02), fat mass (kg) (β = −0.28, 95% CI = −0.56 to −0.01, p  = 0.03), visceral fat area (β = −5.68, 95% CI = −9.55 to −1.80, p  = 0.004). The other measures that appear to be suggestively related to this interaction (0.05 <  p  < 0.07) are waist circumference, waist‐to‐height ratio, trunk fat (%), trunk fat (kg), fat mass (%) and fat mass index. Conclusions: The interaction between MC4R rs17782313 and the AHEI can be related to central and general obesity indices in overweight/obese women. Key points: The present study is related to the hot topic of precision nutrition reporting. The study investigated the interaction between the Alternative Healthy Eating Index and MC4R rs17782313 gene variants and their association with central and general obesity indices in women. A 147‐item food frequency questionnaire was used for the dietary assessment, genotype single‐nucleotide polymorphisms were evaluated by the polymerase chain reaction‐restricted length polymorphism method, and body composition was also assessed using an InBody 770 scanner. The gene–diet interaction was related to a lower hip circumference, body mass index, fat mass, and visceral fat area in participants.